THE INFLUENCE OF LEADERSHIP ORGANIZATION TOWARDS THE COHESION OF TUBERCULOSIS CONTROL TEAM: A CROSS-SECTIONAL STUDY - Sinta Dewi Lestyoningrum; Rachmawati; Asnan Prastawa (JPH RECODE (Journal of Public Health Research and Community Health Development), 2023)
Background: Leadership is central in a team to carry out the task with optimal results. The Tuberculosis (TB) control team's average achievement in Surabaya from 2015 to 2018 was still below the target (78,23%). Purpose: To conducted to analyze the influence of organizational leadership's perception on the cohesion of the TB control team. Methods: This study was observational with a cross-sectional design and implemented in 43 TB control teams at Surabaya Primary Health Center. The number of informants was 319 team members. The data was obtained with a questionnaire that was processed descriptively and linear regression analysis with SPSS version 25.0. Results: The result showed that organizational leadership had no significant influence on the cohesion of TB control team (p-value 0,124 > α = 0,05). Conclusion: organizational leadership had no significant influence on the cohesion of the TB control team.